Review Article: Body lotion Dari Berbagai Ekstrak Tanaman - Nia Yuniarsih; Ainun Mar’atus Putri Warsito; Dinda Dinanti; Elista Indah Susanti; Mentari Mentari; Muhammad Zein Latif; Refriyanti Irma; Rifah Alena Rades (Journal of Pharmaceutical and Sciences, 2023)
Body lotion is an emulsion cosmetic preparation consisting of two liquids that do not mix with each other. Its function is to care for the body, both to protect and dehydrate the skin due to environmental influences. The mechanism of action of body lotion is to attract water in the air which enters the dehydrated stratum corneum due to the evaporation of water from the skin so that from this process the skin can be moisturized again. The method used in this research is to search databases taken from various scientific articles through PubMed, Science Direct, and Google Scholar. The results of this research show that from the various data obtained the result is that body lotion can be made from various plant extracts because plants have a lot of chemical compounds that are useful as antioxidants, vitamin C and others